Dual Defocused Laser Pyrolysis: A Lasing‐Centric Strategy for Defect and Morphological Optimization in Microsupercapacitor Electrodes. Issue 6 (23rd April 2022) - Yan, Wenrong; Hu, Haibo; Wang, Lei; Ho, Derek
Abstract: Laser‐induced graphene (LIG) has shown great potential for controllable and scalable realization of microsupercapacitors (MSCs). However, as is well‐known, LIG electrodes suffer from low charge storage capacity and conductance. In this paper, a lasing‐centric method is presented for defect control and morphological enhancement in LIG electrodes through unique dual laser pyrolysis. This method encompasses dual lasing pyrolysis, one for the synthesis of defocused LIG, and another for the decoration of Ru nanoparticles to enhance electrochemical performance. Fundamentally, the investigation simultaneously optimizes for defocused lasing distance and lasing speed, which to the best of the author's knowledge, has not been previously reported. The defocused LIG electrode exhibits a remarkably improved electrochemical capacitance of over 25 times (114 mF cm −2 ) compared to the one based on focused laser‐induced graphene (FLIG). As a device demonstration, a flexible and self‐healable MSC has been fabricated based on DFLIG/Ru‐PEDOT/Au electrodes, exhibiting a high areal specific capacitance (25.7 mF cm −2 ), excellent electrochemical stability (91% retention of specific capacitance after 8000 cycles), and good self‐healing performance (85.6% retention of specific capacitance after two cut‐heal cycles). By enhancing material properties via dual defocused laser pyrolysis, this work presents a strategy for highly controllable and scalable realization of electrodes in micro‐energy storage devices. Abstract : A dual defocused laser pyrolysis technique is proposed to optimize for defects and morphology of laser‐induced graphene electrodes. Flexible and self‐healable microsupercapacitors are realized using a two‐step laser‐centric approach, which exhibits significantly enhanced energy storage capacity and rate performance.